Estimation of hematological parameters and lipid profile of coronary artery disease patients with Helicobacter pylori - Alhasan, Muntadher; Manal Badi Salih, (University of Thi-Qar Journal of Science, 2023)
Helicobacter pylori infection causes generally gastric illnesses, however from the beginning of 1994, a few researchers have detailed a relationship of H. pylori with other systemic manifestations are outside stomach include various extra gastric appearances, for e.g., neurological, dermatological, hematologic, visual, cardiovascular, metabolic, hypersensitive, and hepatobiliary diseases. In this study, blood parameters, lipid profile, and fasting glucose were measured for patients with coronary artery disease with H. pylori, and the relationship of H. pylori with lipids, which is considered a risk factor for coronary artery disease, was measured. 150 people participated in the current study, and they were divided into three groups: The first group had arterial disease. coronary artery disease with H. pylori 50 people, the second group had coronary artery disease without H. pylori 50 people, the third group the control group 50 people. The samples were obtained from the heart center in Nasiriyah. Risk factors were taken into account: which included age, gender, smoking status, high blood pressure, and diabetes. In the first group, the number of males was 28 (56%) and females 22 (44%) with an average age of 72.60 ± 18.97, the second group had a number of males 33 (66%) and females 17 (34%) with an average age of 71.70 ± 21.06, the third group the number of males was 28 (56%) and females 22 (44%) with an average age of 55.44 ± 18.53.